An investigation into grammatical metaphor in english and vietnamese political speeches - Dương,Thị Minh Hiền (2014)
This thesis aims at investigating the grammatical metaphor in English and Vietnamese political speeches. The data for analysis in this thesis are 300 samples in political speeches collected from official websites and literary works of famous leaders mainly in the United States and Vietnam. The investigation is carried out based on the theories of grammatical metaphor under the light of functional grammar and a combination of a variety of methods such as descriptive, comparative, contrastive, analytic and inductive. The investigation focuses on analyzing political speeches in terms of ideational metaphor and interpersonal metaphor. The findings of this investigation are clearly presented based on a survey of 300 English and Vietnamese samples of political speeches. By comparing grammatical metaphor in these two languages, we work out the similarities and differences on linguistic properties. This exploration enables us to have a better understanding of grammatical metaphor in English and Vietnamese and helpful to the reading or to the translating of political discourses to some extent.